Negative stiffness honeycombs for recoverable shock isolation. Issue 2 (16th March 2015) - Correa, Dixon M; Klatt, Timothy; Cortes, Sergio; Haberman, Michael; Kovar, Desiderio; Seepersad, Carolyn
Abstract : Purpose: – The purpose of this paper is to study the behavior of negative stiffness beams when arranged in a honeycomb configuration and to compare the energy absorption capacity of these negative stiffness honeycombs with regular honeycombs of equivalent relative densities. Design/methodology/approach: – A negative stiffness honeycomb is fabricated in nylon 11 using selective laser sintering. Its force-displacement behavior is simulated with finite element analysis and experimentally evaluated under quasi-static displacement loading. Similarly, a hexagonal honeycomb of equivalent relative density is also fabricated and tested. The energy absorbed for both specimens is computed from the resulting force-displacement curves. The beam geometry of the negative stiffness honeycomb is optimized for maximum energy absorption per unit mass of material. Findings: – Negative stiffness honeycombs exhibit relatively large positive stiffness, followed by a region of plateau stress as the cell walls buckle, similar to regular hexagonal honeycombs, but unlike regular honeycombs, they demonstrate full recovery after compression. Representative specimens are found to absorb about 65 per cent of the energy incident on them. Optimizing the negative stiffness beam geometry can result in energy-absorbing capacities comparable to regular honeycombs of similar relative densities. Research limitations/implications: – The honeycombs were subject to quasi-static displacement loading. To study shock isolation under impact loads, force-controlled loading is desirable. However, the energy absorption performance of the negative stiffness honeycombs is expected to improve under force-controlled conditions. Additional experimentation is needed to investigate the rate sensitivity of the force-displacement behavior of the negative stiffness honeycombs, and specimens with various geometries should be investigated. Originality/value: – The findings of this study indicate that recoverable energy absorption is possible using negative stiffness honeycombs without sacrificing the high energy-absorbing capacity of regular honeycombs. The honeycombs can find usefulness in a number of unique applications requiring recoverable shock isolation, such as bumpers, helmets and other personal protection devices. A patent application has been filed for the negative stiffness honeycomb design.